Characterization of onion soft rot bacteria in Bangladesh (Bangladesh Journal of Scientific and Industrial Research, 2017)
A study was undertaken for characterization and identification of the soft rot causing bacterial pathogens of onion. Bacterial pathogens were isolated from soft rotted stored onions of different varieties and locations of Bangladesh. Altogether 73 bacterial isolates were isolated from soft rotted onions. Among them, twelve soft rot-positive isolates were selected for characterization and identification on the basis of more virulence. Physiological and biochemical tests were performed following standard methods for characterization and identification of selected soft rot bacterial isolates. Seven isolates namely O-03, O-18, O-69, O-72, O-130, O-156 and O-180 were identified as Pectobacterium carotovorum subsp. carotovorum (E. carotovora subsp. carotovora), two isolates O-101 and O-118 were identified as E. chrysanthemi and three isolates O-05, O-14 and O-15 were the members of Burkholderia cepacia.Bangladesh J. Sci. Ind. Res. 52(3), 209-220, 2017